Selective complexation of divalent cations by a cyclic α, β-peptoid hexamer: a spectroscopic and computational study. Issue 48 (2nd November 2016) - De Santis, E.; Edwards, A. A.; Alexander, B. D.; Holder, S. J.; Biesse-Martin, A.-S.; Nielsen, B. V.; Mistry, D.; Waters, L.; Siligardi, G.; Hussain, R.; Faure, S.; Taillefumier, C.
Abstract : The first report on metal binding ability of a cyclic α, β-peptoid hexamer towards a selection of metal cations is presented. Abstract : We describe the qualitative and quantitative analysis of the complexation properties towards cations of a cyclic peptoid hexamer composed of alternating α- and β-peptoid monomers, which bear exclusively chiral ( S )-phenylethyl side chains (spe) that have no noticeable chelating properties. The binding of a series of monovalent and divalent cations was assessed by 1 H NMR, circular dichroism, fluorescence and molecular modelling. In contrast to previous studies on cations binding by 18-membered α-cyclopeptoid hexamers, the 21-membered cyclopeptoidcP1 did not complex monovalent cations (Na +, K +, Ag + ) but showed selectivity for divalent cations (Ca 2+, Ba 2+, Sr 2+ and Mg 2+ ). Hexacoordinated C-3 symmetrical complexes were demonstrated for divalent cations with ionic radii around 1 Å (Ca 2+ and Ba 2+ ), while 5-coordination is preferred for divalent cations with larger (Ba 2+ ) or smaller ionic radii (Mg 2+ ).